Analisa Kemampuan Membayar Tarif Angkutan Umum - Gare, Mansuetus (TEKNOSIAR, 2022)
The determination of public transportation rates in the North Ende District area is something that is dancingto be studied. It should be noted that the population in Ende Subdistrict consists of students, students,traders, civil servants, laborers, farmers. So there are still many variables that affect and involve variousparties. The research methodology by conducting interviews and questionnaires is spread across 7 zones.The data collected includes the desire of passengers to get the cheapest fares and public transport operators.For this reason, studies in determining the initial tariff and adjusting tariffs need to be carried outmeasurable studies. In the study, it found that the operational cost of the vehicle (BOK) was Rp.385,695.44.4% of transportation services are students with a rate of Rp.1,400 and 55.56% of general use at a rate ofRp.2,800. The average freight fare is Rp.2,175. Meanwhile, the ability of transportation users to pay tariffs isaround Rp.1,400 to Rp.2,600. And the willingness to use public transportation to pay a tariff of Rp.1,000 toRp.2,600. An average of Rp.1888 means that 24.25% of user will is below average value and 75.75% will isabove average. The conclusion of the tariff determination in North Ende sub-district is still within the normlimit where the student fare is IDR 1,400 and general passengers are IDR 2,800. It is not much different fromthe ability and willingness to use public transport.